PELAKSANAAN PENANGGULANGAN BENCANA BANJIR OLEH BADAN PENANGGULANGAN BENCANA DAERAH KOTA DUMAI TAHUN 2021 - Ramadhani, Desy; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Dumai City is one of the twelve regencies/cities in Riau Province. Where the city of Dumai is located at position 01º 23'00" - 01º 24'23" North Latitude 101º23'37" - 101º28'13" East Longitude. With an area of 1,727.38 Ha and a water area of 71,393 Ha. The location of Dumai City which is on the coast makes Dumai City a disaster-prone area. Law No. 24 of 2007 concerning Disaster Management, a disaster is an event or series of events that threatens and disrupts people's lives and livelihoods caused either by natural factors or non-natural or human factors, resulting in human casualties, environmental damage, loss of property and psychological impacts. Natural disasters are disasters caused by nature, including earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes and landslides. This study uses the theory of elements of coordination. Coordination is an element of the orderly arrangement of group efforts to create commonalities of action in pursuit of common goals. Coordination includes Internal Coordination and External Coordination. The elements of coordination as stated by James D. Money consist of Agency Effort, Unity of Action, Common Purpose. The results of this study indicate that the Dumai City Regional Disaster Management Agency has carried out coordination with good to all agencies related to the natural flood disaster that occurred in 2021. However, there are several obstacles, namely differences in institutional status which are further obstacles, the lack of facilities and infrastructure is also an obstacle for the Dumai City Regional Disaster Management Agency. Keywords: Implementation, Coordination, Natural Disasters